2019
DOI: 10.15237/gida.gd19162
|View full text |Cite
|
Sign up to set email alerts
|

Use of Kefir in Cokelek Cheese Production

Abstract: Çökelek peyniri, yoğurttan üretilen ve daha çok semt pazarlarında satışı yapılan geleneksel bir peynir çeşididir. Çalışmada çökelek peyniri üretiminde kefir kullanımının uygunluğu araştırılmıştır. Yoğurt ve kefirden elde edilen çökelek peynirleri (YÇ, KÇ) fizikokimyasal, mikrobiyolojik ve duyusal nitelikleri yönünden 1., 14. ve 28. günlerde karşılaştırmalı olarak incelenmiştir. Yoğurt ve kefir kullanılarak üretilen çökelek peynirlerinde toplam kurumadde, kül, tuz ve protein değerleri bakımından önemli bir fark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
1
0
0
Order By: Relevance
“…Şanlı and Anlı (2020) reported that TAMB count of Çökelek samples changed from 3.31 log CFU g -1 to 3.58 log CFU g -1 during 28 days of storage. The obtained results in the study are similar to those determined by Öksüztepe et al [18] but were higher compared to those found by Çardak [1] and Şanlı and Anlı (2020).…”
Section: Microbiological Propertiessupporting
confidence: 89%
“…Şanlı and Anlı (2020) reported that TAMB count of Çökelek samples changed from 3.31 log CFU g -1 to 3.58 log CFU g -1 during 28 days of storage. The obtained results in the study are similar to those determined by Öksüztepe et al [18] but were higher compared to those found by Çardak [1] and Şanlı and Anlı (2020).…”
Section: Microbiological Propertiessupporting
confidence: 89%